Chemical abundances and evolutionary status of some lambda Bootis type stars and FBSwl. - Chernyshova, I. V. (Одеські астрономічні публікації, 2017)
Comparative analysis of chemical abundances in the atmospheres of lambda Bootis type stars and FBSwl (field blue stragglers week lined) is presented. Evolutionary status of these metal deficient stars is discussed.